New appointment - Sunday, Star (Sunday Star, 2012)
ASSOC Prof Dr Abdul Malek Abdul Karim has been appointed deputy vice-chancellor (Student Affairs and Alumni) at Universiti Utara Malaysia (UUM) for a period of three years effective Dec 7.